EFL STUDENTS' SELF-EFFICACY AND ONLINE PRESENTATION PERFORMANCE: CORRELATIONAL STUDY (RETAIN, 2020)
The relationship between self-efficacy and online presentation performance is one of the less researched topics; that is why this study was conducted to investigate the relationship between presentation selfefficacy and online presentation performance of the EFL students in higher education. The current study uses two instruments which are self-efficacy questionnaire to obtain presentation self-efficacy level of the students and also the document which consists of students’ online performance scores. The presentation self-efficacy level of the students was gained before the students doing an online presentation, while the students’ presentation score was assessed by the lecture using their own assessment rubric. Those data from 20 EFL students of Academic Speaking Class A in Universitas Negeri Suarabaya were analyzed in order to find out whether those two variables were affected by each other. The result of this study showed that both variables indicate no correlation toward each other because of some reason. First, the main reason is because of the change in the learning circumstance during the COVID-19 outbreak. The unexpected changes in the situation which forced the students to do an online presentation instead of face-to-face presentation was affected self-efficacy level. The second reason is the students’ previous experience in performing an online presentation. Those who experienced in the necessary situation will be more confident to do the second performance, compared with those who have not experienced yet. Keywords: Self-efficacy, online presentation performance, foreign language students